Squandering 'green' opportunities - Abd Razak, Dzulkifli (2009)
ON the eve of the G20 London Summit last week, two significant international meetings related to education took place backtoback in Europe. One was the Commonwealth Educational Cooperation at the University of Oxford; the other was the UNESCO World Conference on Education for Sustainable Development in Bonn. Fittingly, the former celebrates the first Commonwealth Education Conference held in Oxford some 50 years ago. Indeed, the Commonwealth is often said to rest on the three pillars of language, law and education, each reflecting one another.